Systematic review of topical capsaicin for the treatment of chronic pain - Mason, L; Moore, R; Derry, S; Edwards, J; McQuay, H (BMJ Publishing Group, 2004)
Objective: To determine the efficacy and safety of topically applied capsaicin for chronic pain from neuropathic or musculoskeletal disorders. Data sources: Cochrane Library, Medline, Embase, PubMed, an in-house database, and contact with manufacturers of topical capsaicin. Study selection: Randomised controlled trials comparing topically applied capsaicin with placebo or another treatment in adults with chronic pain. Data extraction: Primary outcome was dichotomous information for the number of patients with about 50% reduction in pain. Outcomes were extracted at four weeks for musculoskeletal conditions and eight weeks for neuropathic conditions. Secondary outcomes were adverse events and withdrawals due to adverse events. Data synthesis: Six double blind placebo controlled trials (656 patients) were pooled for analysis of neuropathic conditions. The relative benefit from topical capsaicin 0.075% compared with placebo was 1.4 (95% confidence interval 1.2 to 1.7) and the number needed to treat was 5.7 (4.0 to 10.0). Three double blind placebo controlled trials (368 patients) were pooled for analysis of musculoskeletal conditions. The relative benefit from topical capsaicin 0.025% or plaster compared with placebo was 1.5 (1.1 to 2.0) and the number needed to treat was 8.1 (4.6 to 34). Around one third of patients experienced local adverse events with capsaicin, which would not have been the case with placebo. Conclusions: Although topically applied capsaicin has moderate to poor efficacy in the treatment of chronic musculoskeletal or neuropathic pain, it may be useful as an adjunct or sole therapy for a small number of patients who are unresponsive to, or intolerany of, other treatments.